Racial group, socioeconomic status, and the development of persistent proteinuria in systemic lupus erythematosus. Issue 2 (1st February 2000) - Hopkinson, N D; Jenkinson, C; Muir, K R; Doherty, M; Powell, R J
Abstract : OBJECTIVES: Systemic lupus erythematosus (SLE) patients of Afro-Caribbean and Asian origin living in the United Kingdom have a more severe spectrum of disease compared with the white population but whether this is attributable to genetic host factors or environmental factors is unclear. This study examines time from first symptom to onset of persistent proteinuria, as a marker of renal disease, to assess which factors are important. METHODS: The 189 patients studied were ascertained using multiple methods and included 161 white, 22 Afro-Caribbean and six Asian patients. Time of first observation of persistent proteinuria (⩾0.5 g/day) was taken as onset of renal SLE. Initial univariate analysis to determine which factors are associated with onset of renal disease was followed by using a Cox's proportional hazards regression model enabling analysis of several prognostic factors at the same time. Variables included three measures of socioeconomic status, ethnic group and the presence or absence of different autoantibodies. RESULTS: There was no effect from any socioeconomic variable. Using forwards stepwise selection, the following had independent effects (p<0.05) on the development of renal SLE: Afro-Caribbean race (hazard rate ratio 4.4 (1.9–10.2), compared with white population); and the presence of IgG anti-cardiolipin antibodies (hazard rate ratio 2.6 (1.2–5.7)). CONCLUSION: Differing socioeconomic factors do not explain the increased frequency of lupus nephritis in Afro-Caribbean patients with SLE, but rather there are important genetic or other host differences. The independent effect of IgG anti-cardiolipin antibodies warrants further investigation.